Odpowiedzi

Najlepsza Odpowiedź!
2009-11-29T19:55:38+01:00
A)
5y=2
x+y=2 2/5

y=2/5
x+ 2/5 =2/5

y=2/5
x=0

B)
4y-x=6
17y=0

4y-x=6
y=0/17

4y-x=6
y=0

4*0-x=6
y=0

-x=6
y=0

x=-6
y=0

C)
a=b
2a+b=9

a=b
2b+b=9

a=b
3b=9

a=b
b=3

a=3
b=3

;)

1 5 1
2009-11-29T20:10:53+01:00
A)
5y=2
x+y=2 2/5

5y=2
y=2 2/5-x

5*((12/5)-x)=2
12-x=2
x=10

y=2 2/5-10
y=-7 3/5

b)
4y-x=6
17y=0

4y=6+x /:4
17y=0

y=6/4+1/4 x
17y=0

17(6/4+1/4 x)=0
102/4 + 17/4 x=0 /*4
102+17x=0
17x=-102
x-6

y=6/4 + (-6/4)
y=0


c)
a=b
2a+b=9
2b+b=9
3b=9
b=3
a=3
1 5 1
2009-11-29T20:15:18+01:00
A)5y=2
y=2:5=0,4
y+x=2 2/5
x=2 2/5-0,4=2

B)17y=0
y=17:0=0
4y-x=6
4*0-x=6
0-(-6)=6

C)a=b
2a+b=9
2a+a=9
3a=9
9:3=3
a=3
2*3+3=9

1 3 1